External Morphological Study of Saprinus discoidalis Le Conte (Coleoptera: Histeridae) New Record to Iraq - Hussein, Azhar A.M.; Al-Asady, Hassan S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
External Morphological study of  species Saprinus discoidalis of subfamily saprininae from family Histeridae of the order coleopteran. The specements of  the present study were collected from Salahdin Governor-ate (Beigi &Balad) and Governorate during May 2012.         The present study included detailed description of most body parts (Head, Thorax, Abdomen and their appendages) identification and recognition of species study male genitalia. The species Saprinus discoidalis LeConte is a new record to Iraqi fauna of Coleoptera.